SMES SEPAK TAKRAW TRAINING MODEL BASED ON A HIGH-STORED HANGING BALL FOR BEGINNING SEPAK TAKRAW ATHLETE - Jufrianis, Jufrianis; Rizki, Elfera; Permatha Sari, Vigi Indah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
The aim of this research is to find out how effective the influence of the Tiered Hanging Balls-Based Smes Sepak Takraw Training Model is on Beginner Sepak Takraw Athletes. An experiment with a one-group pre-test-treatment-post-test design was used for this research. Based on the results of the effectiveness test using the t-test above, from the difference in pretest results, the price tO = 10.532 is greater than the price tt = 0.000 and the posttest value is obtained, the price tO = 19.105 is greater than the price tt = 0.000 (at a significance level of 0.05), then the null hypothesis is rejected. So it can be concluded that, there is a significant difference between the pretest and posttest test results of the Smes Sepak Takraw training program based on Tiered Hanging Balls for beginner sepak takraw athletes. From this research data, the average pretest price with mean = 1.326 is smaller than the posttest average = 1.805. Thus, it can be stated that the Smes Sepak Takraw training program based on Tiered Hanging Balls is effective for using Balls on beginner sepak takraw athletes in Kampar-Riau district. So it can be concluded that the results of this research can improve smash results in sepak takraw for beginner athletes based on Tiered Hanging Balls.